Pembentukan Reputasi Desa Adat Using Kemiren melalui Image Rumah Adat Using - Ayu Wanda Febrian; Nadia Romadhoni; Rahmatul Laili Cahyaning Asri; Frida Sucila Hartini; Adetiya Prananda Putra; Arik Fajar Cahyono (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The traditional House is a building that has a structure, preparation, form and function accompanying motif that has its own characteristics. One of the tribes that have a distinctive custom homes i.e. Using existing tribes in the region of Banyuwangi Regency. Custom homes Using formerly in many Indigenous Villages Using Kemiren, Kecamatan Glagah, Banyuwangi. The condition of Using custom homes at this time greatly reduced capacity due to the development of modern homes, so that the Indigenous Village of cultural heritage Using Kemiren in the form of custom homes are increasingly eroded. It is expected the public can participate in a government program Using Custom Kemiren Village in order to maintain the cultural identity of the tribe Using and custom homes Using be brand image of Village Customs Using Kemiren. Therefore the author does this research as a form of Indigenous Village reputation formation Using Kemiren through the image Using custom homes. Keywords: Brand image, making reputation, village customs Using Kemiren, Using Customs Homes